Significado atribuido al diagnóstico y evolución de diabetes mellitus tipo 2 en progenitores pertenecientes al ciclo familiar con hijos adultos (2019)
This research work aims to analyze the meaning attributed to the diagnosis and evolution of type 2 diabetes mellitus in parents belonging to the family life cycle with adult children, since this is a chronic disease that mainly affects blood glucose levels, causing alterations in physical and psychological functions on a personal, family and social level.